Language Teaching Materials for Writing Advertising Texts - Muhamad Faisal Assyuza; Miftahulkhairah Anwar; Gusti Yarmi (Journal La Sociale, 2024)
This study is based on extensive library research, utilizing a wide range of information and resources from various sources. Having the right instructional materials is crucial for the successful completion of any academic program, including Indonesian language classes. Junior high school Indonesian language classes in Class VIII explore a range of subjects, one of which is the art of crafting advertisement copy. To achieve optimal outcomes, it is crucial to utilize appropriate instructional resources while acquiring proficiency in the Indonesian language for advertising purposes. This research aimed to provide a comprehensive description of the different types of advertisements that can be utilized as teaching materials in Indonesian language courses, along with an exploration of the diverse concepts associated with these materials.